Trade Facilitation, Value Creation, and Competiveness : Policy Implications for Vietnam's Economic Growth, Summary Report - Pham, Duc Minh; Mishra, Deepak; Cheong, Kee-Cheok; Arnold, John; Trinh, Anh Minh; Ngo, Huyen Thi Ngoc; Nguyen, Hien Thi Phuong (World Bank, Washington, DC, 2014)
This report explores the role of trade facilitation and logistics in driving export and ultimately national competitiveness. It posits that this area of trade consists of three interrelated pillars: (i) transport infrastructure and logistics services; (ii) regulatory procedures for exports and imports; and (iii) supply chain organization. Transport infrastructure and logistics services relate to the physical aspects of trade flows. Logistics services include a variety of services, the most important of which are transportation, storage and consolidation. This summary is organized into nine sections. After the introduction, section two presents the conceptual framework for this study. The economic context under which trade facilitation is discussed is outlined in section three. It describes Vietnam's evolving structure of trade and competitiveness. The country's trade logistics is part of this structure and this is germane to understanding the key issues and solutions proposed. This is followed by discussion of the three pillars of trade facilitation in sections four to six and then section seven presents the institutional framework underpinning these pillars. Section eight then pulls together the diverse roles of government, such as setting policies, acting as regulator, and being the facilitator working in collaboration with key stakeholders. The conclusion, section nine, suggests a set of recommendations.